Trade Liberalization, Poverty and Inequality - Dubey, Shivendra Kumar (International Journal of Scientific Research and Management (IJSRM), 2015)
:The question of how trade liberalization affects poverty and inequality remains largely an empirical one. Work has attempted toaddress the question, focusing mostly on the effect of trade liberalization on within-country income inequality. Work has attempted toaddress the question, focusing mostly on the effect of trade liberalization on within-country income inequality. Studies using cross-countryvariation typically find little relationship between trade liberalization and levels or rates of change of inequality. India presents aparticularly relevant setting in which to seek the answers to these questions. First, India is the home of one-third of the worlds poor. Second,the nature of India’s trade liberalization—sudden, comprehensive, and largely externally imposed facilitates a causal interpretation of thefindings. India liberalized its international trade as part of a major set of reforms in response to a severe balance-of-payments crisis in 1991.On trade policy, benchmarks Trade Liberalization, Poverty, and Inequality 295 for the first review of the standby arrangement included areduction in the level and dispersion of tariffs and a removal of a large number of quantitative restrictions. Specific policy actions in anumber of areas notably industrial deregulation, trade policy and public enterprise reforms, and some aspects of financial-sector reformalso formed the basis for a World Bank Structural Adjustment Loan, as well as sector loans.